Endothelium-dependent vasorelaxation and antiproliferation activities of chloroform extract F5 fraction from Crinum amabile Donn ex Ker Gawl. leaves - Lim, Chung Pin (2019)
Medicinal plants are potential sources of bioactive compounds, which due to their multiple pharmacological benefits, could be developed into promising therapeutic drugs. Crinum amabile possesses various biological activities such as antimalaria, anticancer and antihypertension. These encouraging findings had led to the selection of this plant species as a viable candidate for developments of anticancer and antihypertension products. Therefore, this research was undertaken to investigate the anticancer (cytotoxicity, apoptosis and anti-angiogenesis) and the antihypertensive properties of this plant. The possible pathways to the underlying mechanism of respective activities were also elucidated. Firstly, the leaves of C. amabile were serially extracted using Soxhlet’s apparatus to yield four different extracts: petroleum ether extract (PE), chloroform extract (CE), methanol extract (ME) and water extract (WE). Preliminary assays (both anticancer and vasorelaxation) showed that CE exhibited the highest pharmacological effects. Thus, CE was fractionated using column chromatography and standardized through thin layer chromatography to produce six individual fractions. Next, the cytotoxicity of all these extracts and fractions were tested on various human cancer cell lines using MTS cytotoxicity assay. Results indicated that F5 fraction exhibited non-cell-specific cytostatic effects on most of the cancer cell lines, with MCF-7 breast cancer cells being the most susceptible. However, further studies using two apoptosis assays: annexin-V and DNA fragmentation assay showed that F5 fraction did not induce cell apoptosis on MCF-7 cells and no DNA fragmentations were detected. Nonetheless, cell proliferation assay using MTT assay revealed that F5 fraction was able to inhibit normal cell proliferation as well as VEGF-induced cell proliferation of normal endothelial cell: HUVECs. Data from this study illustrated that F5 fraction from leaf CE of C. amabile was able to exhibit cytostatic effect through anti-proliferation and anti-angiogenesis activities rather than induction of cell apoptosis. Meanwhile the vasorelaxation activities of C. amabile extracts and fractions were elucidated on both phenylephrine pre-contracted intact and denuded rat aortic rings. The results indicated that F5 fraction exhibited the highest vasorelaxation activities and produced both endothelium-dependent and endothelium-independent vasorelaxation. In depth studies of its mechanism pathway(s) elucidated that the endotheliumdependent vasorelaxation induced by F5 fraction was primarily achieved through the stimulation of PGI2 production and partial association with NO/sGC/cGMP activation pathway. The study proposed that C. amabile can serve as a promising lead candidate for both discovery and development of new cytotoxic or vasodilator drugs.